PENGARUH KUALITAS BAKERY TERHADAP KEPUASAN PELANGGAN RESTORAN WEDANG JAHE DI NUSA DUA BEACH HOTEL & SPA - Simon Rico Briantono; I Gusti Agung Bagus Widiantara; Ida Ayu Putu Sulastri (Journal of Tourism and Interdiciplinary Studies, 2021)
Tourism in Indonesia is a growing business, especially in Bali. Bali has been long to be a vacation destination for both local and foreign tourists. It has contribution to business development in the tourism industry, including hotels and restaurants. In an effort to win the market competition, of course the tourism industry has done various things. This is the background of the research conducted by the writer at Nusa Dua Beach Hotel & Spa. The purpose of the study is to determine the effect of bakery quality. The writer uses quantitative analysis and also SPSS program to explain the correlation between bakery quality and customer satisfaction. The result found that (a) there is a very strong relationship between the quality of bakery and customer satisfaction of Wedang Jahe Restaurant at Nusa Dua Beach Hotel & Spa, (b) the quality of the bakery has impacted customer satisfaction aa much as 85,6 % which shows strong influenced, but there is still other factor impacted it which is not analysed in this study